The balbyter ant Camponotus fulvopilosus combines several navigational strategies to support homing when foraging in the close vicinity of its nest - Yilmaz, Ayse; Gagnon, Yakir; Byrne, Marcus J.; Foster, James J.; Baird, Emily; Dacke, Marie (Frontiers in Integrative Neuroscience, 2022)
Many insects rely on path integration to define direct routes back to their nests. When shuttling hundreds of meters back and forth between a profitable foraging site and a nest, navigational errors accumulate unavoidably in this compass- and odometer-based system. In familiar terrain, terrestrial landmarks can be used to compensate for these errors and safely guide the insect back to its nest with pin-point precision. In this study, we investigated the homing strategies employed by Camponotus fulvopilosus ants when repeatedly foraging no more than 1.25 m away from their nest. Our results reveal that the return journeys of the ants, even when setting out from a feeder from which the ants could easily get home using landmark information alone, are initially guided by path integration. After a short run in the direction given by the home vector, the ants then switched strategies and started to steer according to the landmarks surrounding their nest. We conclude that even when foraging in the close vicinity of its nest, an ant still benefits from its path-integrated vector to direct the start of its return journey.